Students’ Perception and Social Acceptance towards Lecturers with Diffability (Different Ability) - Muhammad, Rifqi; Mualimin, Mualimin (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2024)
Employing disabled lecturers on campus necessitates an inclusive culture which can be achieved through positive social perception and student acceptance. This study aims to (1) examine the relationship between student perception and social acceptance of disabled lecturers; (2) describe the differences in student perception and social acceptance based on gender. A quantitative survey approach was employed, with the study conducted at the IAIS Sambas campus, Indonesia. The respondents comprised 102 active students from the Faculty of Da'wah and Humanities. Data analysis included correlation analysis, t-tests, and ANOVA. The results of this study indicate: (1) a positive and very strong correlation (r = 0.626) between student perception and social acceptance of disabled lecturers, and 2) that female students have more favorable perceptions and higher social acceptance of disabled lecturers compared to male students. These results contribute empirically to the field of inclusive education in Indonesia, particularly within Islamic religious colleges.